Salivary Oxidative Stress Markers in Relation to Vascular Disease Risk of Type Two Diabetes Mellitus - Dalia K Abbas; Dalia K El-Samarrai (College of Dentistry/ University of Baghdad, 2016)
Background: Cardiovascular disease (CVD) is an important complication of type 2 diabetes mellitus (T2DM). Oxidative stress plays a major role in the development of CVD. Saliva has a diagnostic properties aiding in the detection of systemic diseases. This study aimed to assess the association between salivary oxidative stress markers and the risk of vascular disease (VD) in T2DM patients. Materials and Methods: One hundred T2DM patients and fifty apparently healthy males were enrolled in this study. Saliva sample was collected for assessment of oxidative stress markers including: lipid peroxidation plasma thiobarbituric acid-reactive substances (TBARS), uric acid (UA) and total antioxidant capacity (TAC) levels. Arterial stiffness index (ASI) was used for the assessment of VD risk. Results: According to ASI, T2DM patients were categorized into two groups: Group A: T2DM patients without VD risk. Group B: T2DM patients with VD risk. The mean values of TBARS and UA of group B showed a statistically highly significant elevation compared to group A and controls (P